Systematic review on emotional intelligence and well-being in adolescents: evidence and challenges - Ruíz-Ortega, Ana M.; Berrios Martos, Pilar (Escritos de Psicología - Psychological Writings, 2023)
Educational environments show an increasing interest in the development of emotional intelligence in adolescents, due to the growing evidence of its association with well-being and its consequential impact over the lifetime. However, the diversity of theoretical models and instruments used to measure both constructs make it difficult to draw conclusions about this relationship. Therefore, the main objective of this study has been to systematically review the state of knowledge in recent years on the relationship between emotional intelligence and well-being in adolescents. A search was carried out in the Web of Science and Scopus databases and 47 articles were selected that met this study’s inclusion criteria. The results indicate that adolescents with more emotional intelligence register higher levels of subjective and psychological well-being. These results are discussed and the main educational challenges are analysed.